2018
DOI: 10.1016/j.techfore.2017.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, entrepreneurial, knowledge, and business ecosystems: Old wine in new bottles?

Abstract: Rooted in the territorial approach, this theoretical paper offers a systematic literature review (SLR) of ecosystems based on a selection of 104 articles and books and their archetypes. First, we identify and discuss the four main types of ecosystems-business, innovation, entrepreneurial, and knowledge ecosystems-and indicate the presence of other transversal concepts. Second, we provide an overview of related and well-established theories from the territorial approach that have been largely omitted although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(223 citation statements)
references
References 154 publications
2
163
0
3
Order By: Relevance
“…Web of Science (WoS) was the preferred database to search the literature for several reasons. First, compared to other databases such as Google Scholar, WoS provides the highest number of high quality journals and articles (as cited in Scaringella & Radziwon, 2017) and reliability (Augillo and Falagas, as cited in Prins et al, 2016). Second, Gavel and Iselid (2008) quantitatively showed that the coverage of WoS in social science and humanities is broader than SCOPUS.…”
Section: Identifyingthe Literature 211 Choice Ofdatabasementioning
confidence: 99%
“…Web of Science (WoS) was the preferred database to search the literature for several reasons. First, compared to other databases such as Google Scholar, WoS provides the highest number of high quality journals and articles (as cited in Scaringella & Radziwon, 2017) and reliability (Augillo and Falagas, as cited in Prins et al, 2016). Second, Gavel and Iselid (2008) quantitatively showed that the coverage of WoS in social science and humanities is broader than SCOPUS.…”
Section: Identifyingthe Literature 211 Choice Ofdatabasementioning
confidence: 99%
“…innovation, knowledge) in many of its characteristics, e.g. : the diversity of actors involved, goals ranging from knowledge-related goals, to economic goals, to social goals, and the territorial scope (Scaringella and Radziwon 2018). Second, the ecosystem literature holds findings on governance, particularly regarding the orchestration (or leadership) of ecosystems, that may be informative to smart cities.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the ecosystem literature holds findings on governance, particularly regarding the orchestration (or leadership) of ecosystems, that may be informative to smart cities. Third, the literatures share the same challenges when it comes to developing an understanding of what Scaringella and Radziwon (2018) call "life cycle guidelines for practitioners and […] scholars" (p.74), or in other words: What do policy makers and managers in these ecosystems and smart cities need to do in order for their projects to be sustainable in the long run?…”
Section: Introductionmentioning
confidence: 99%
“…The use of some system-level theoretical concepts such as emergence, interdependence, and dynamics is rather frequent in current scholarly work (see, e.g., Adner & Kapoor, 2010;Ansari et al, 2016;Stam, 2015). However, a more overarching emphasis on system-level theoretical principles and concepts is much rarer (for exceptions and discussion, see, e.g., Peltoniemi, 2006;Ritala & Almpanopoulou, 2017;Roundy et al, 2018;Scaringella & Radziwon, 2017). Second, network theory and social networks were seen as another promising theoretical foundation.…”
Section: What Is the Biggest Challenge In Conducting Ecosystem Research?mentioning
confidence: 99%